Proposed classification of medial maxillary labial frenum based on morphology - Ranjana Mohan; Pankaj Kumar Soni; Munagala Karthik Krishna; Mohan Gundappa (Wolters Kluwer Medknow Publications, 2014)
Objectives: To propose a new classification of median maxillary labial frenum (MMLF) based on the morphology in permanent dentition, conducting a cross-sectional survey. Materials and Methods: Unicentric study was conducted on 2,400 adults (1,414 males, 986 females), aged between 18 and 76 years, with mean age = 38.62, standard deviation (SD) = 12.53. Male mean age = 38.533 years and male SD = 12.498. Female mean age = 38.71 and female SD = 12.5750 for a period of 6 months at Teerthanker Mahaveer University, Moradabad, Northern India. The frenum morphology was determined by using the direct visual method under natural light and categorized. Results: Diverse frenum morphologies were observed. Several variations found in the study have not been documented in the past literature and were named and classified according to their morphology. Discussion: The MMLF presents a diverse array of morphological variations. Several other undocumented types of frena were observed and revised, detailed classification has been proposed based on cross-sectional survey.